Psychological or Theological Dynamics of Students who Wear Cadar at Islamic Universities in Indonesia - Mayyadah; Jusmiati; Husain, Muhammad Zakin bin (Universitas Islam Negeri Alauddin Makassar, 2024)
Cadar is a type of veil worn by some Muslim women that covers the face, leaving only the eyes visible. Several studies have been carried out with the primary aim of exploring the use of this veil in Islamic colleges. These explorations identified several significant elements contributing to the usage of cadar, including psychological and ideological issues, both of which have not been thoroughly examined. Therefore, the present study aims to fill these gaps through the use of the reality of fiqh and psychological techniques. To achieve the stated objective, data were collected from 22 UIN Datokarama high school graduates who were assigned to participate in lifts, interviews, and focus group discussions (FGDs). The obtained results showed that three factors namely, the need for stability, the possibility of personal development, and the propensity to emulate an adored figure, served as psychologically motivating factors to students. Furthermore, the reality of fiqh was observed to suggest that the use of cadar is not necessarily accompanied by a strong religious understanding of its significance. This fact reinforces previous results that the adoption of cadar in Islamic colleges is more psychological than theological. Within the context of the present study, new facts emphasizing psychological and theological fragility among university students were uncovered and stakeholders are expected to address these facts when dealing with the phenomenon at Islamic universities.